Analisis Potensi Desa dalam Peningkatan Pendapatan Asli Desa di Kabupaten Bolaang Mongondow Timur - Pangkey, Masje Silija; Pombengi, Jericho Danga; Posumah, Johny Hanny (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2024)
The implementation of village government development in East Bolaang Mongondow can be measured based on the ability of each village to generate financial income, namely Original Village Income (PADesa). Village original income consists of business results, asset results, self-help and participation, mutual cooperation and others. To be able to see village independence, it can be measured when the village government is able to manage the village's potential so that it can increase the village's original opinion. East Bolaang Mongondow Regency is the district that has the lowest realized income when compared to other districts in North Sulawesi Province. This income inequality has occurred over the last five years from 2017 to 2022. For this reason, the role of villages in increasing income potential needs to be emphasized. This research aims to identify and map village potentials to increase Village Original Income (PADesa) in East Bolaang Mangondow Regency so that it can contribute to increasing regional income.